Teaching and learning at the intersection of artificial intelligence, academic integrity, and assessment innovation: A rapid scoping review protocol - Holden, Michael; Paisley, Naomi; Healy, Myke; Eaton, Sarah Elaine; Delanoy, Nadia; Burns, Amy (Canadian Perspectives on Academic Integrity, 2025)
For three years, teachers and teacher educators have been struggling to respond to the advent of generative artificial intelligence (GenAI) and its implications for teaching and learning. Building on DeLuca et al.’s (2025) AI3 framework, this paper is situated at the intersections of artificial intelligence, academic integrity, and assessment innovation: three critical ‘AIs’ for the current moment. Owing to a dearth of literature reviews at this intersection, this paper presents a rapid scoping review protocol for AI3 in preservice teacher education. The protocol follows the Joanna Briggs Institute’s updated manual for scoping reviews and the Preferred Reporting Items for Systematic Reviews Meta-Analysis (PRISMA) reporting standards (Aromataris & Munn, 2020). The studies included in the review will be analyzed for insights on these topics, particularly the innovative practices possible in an age of GenAI. Our findings will be relevant to teacher educators in particular and more broadly to educational researchers and practitioners interested in integrity, innovation, and defensible practice in ever-shifting GenAI spaces.